2015
DOI: 10.1007/s10120-015-0505-0
|View full text |Cite
|
Sign up to set email alerts
|

The embryonic Brachyury transcription factor is a novel biomarker of GIST aggressiveness and poor survival

Abstract: Background The T-box transcription factor Brachyury was recently reported to be upregulated and associated with prognosis in solid tumors. Here, we proposed to evaluate the potential use of Brachyury protein expression as a new prognostic biomarker in gastrointestinal stromal tumors (GIST). Methods Brachyury protein expression was analyzed by immunohistochemistry in a cohort of 63 bona fide GIST patients. Brachyury expression profiles were correlated with patients' clinicopathological features and prognostic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 50 publications
(75 reference statements)
0
19
2
Order By: Relevance
“…Tumor cells undergoing this phenotypic transition exhibit enhanced motility and invasiveness in vitro , a propensity to metastasize in vivo , and features of tumor stemness (16), including resistance to a range of therapeutics such as chemotherapy, radiation, small molecule therapies, and, potentially, immunotherapy (1720). In agreement with a role for brachyury in the progression of carcinomas, multiple studies have now shown that the level of brachyury in the primary tumor correlates with poor patient prognosis in carcinomas of the lung (21), colon (6), breast (9), triple-negative breast (10), and gastrointestinal stromal tumor (GIST) (22). Brachyury expression has also been shown to be correlated with advanced-stage prostate cancer (8).…”
Section: Introductionmentioning
confidence: 64%
“…Tumor cells undergoing this phenotypic transition exhibit enhanced motility and invasiveness in vitro , a propensity to metastasize in vivo , and features of tumor stemness (16), including resistance to a range of therapeutics such as chemotherapy, radiation, small molecule therapies, and, potentially, immunotherapy (1720). In agreement with a role for brachyury in the progression of carcinomas, multiple studies have now shown that the level of brachyury in the primary tumor correlates with poor patient prognosis in carcinomas of the lung (21), colon (6), breast (9), triple-negative breast (10), and gastrointestinal stromal tumor (GIST) (22). Brachyury expression has also been shown to be correlated with advanced-stage prostate cancer (8).…”
Section: Introductionmentioning
confidence: 64%
“…In this regard, we and others have shown that the presence of high levels of brachyury in the primary tumor can predict poor prognosis in a range of human carcinomas including lung (Haro et al 2013), hepatocellular (Du, et al 2014), GIST (Pinto, et al 2015), prostate (Pinto et al 2014), colorectal (Kilic et al 2011; Sarkar, et al 2012) and hormone receptor positive breast cancer (Palena et al 2014b). In agreement, here we have observed that high levels of brachyury in primary TNBC tumors associate with poor survival.…”
Section: Discussionmentioning
confidence: 98%
“…Brachyury ( T ) is a T‐box transcription factor family with a central role in notochord and mesoderm specification (Herrmann et al ., ). In the last years, Brachyury has been described by us and others to be upregulated in several solid tumors, including chordoma (Vujovic et al ., ), lung (Roselli et al ., ), breast (Palena et al ., ), colorectal (Kilic et al ., ), prostate (Pinto et al ., ) cancer, and GIST (Pinto et al ., ,b). Importantly, in these tumors, Brachyury has been reported as an independent biomarker of poor prognosis (Kilic et al ., ; Haro et al ., ; Palena et al ., ; Pinto et al ., , ,b).…”
Section: Introductionmentioning
confidence: 99%